2017
DOI: 10.1097/md.0000000000009045
|View full text |Cite
|
Sign up to set email alerts
|

Viable placental allograft as a biological dressing in the clinical management of full-thickness thermal occupational burns

Abstract: Rationale:Occupational burn injuries can be detrimental and difficult to manage. The majority of complex cases are referred and managed at regional burn centers where access to specialized care is available. As an alternative to hospitalization with staged surgical procedures, placental products may be used for outpatient medical management of these common burn injuries, especially if access to a regional burn center is limited or restricted.Fresh amnion has been a treatment of choice in burns for more than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In agreement with our results with lung surfactant, no graft related adverse events were found with amniotic membrane treatment in diabetic foot ulcers 54 , epidermolysis bullosa 55 or in burns 56 . Enhancement of granulation tissue formation and wound closure of arteriosclerotic foot sores or amelioration of atopic dermatitis by topical Alv treatment are preliminary observations of a pilot study that will be investigated in the next phase of clinical trials.…”
Section: Visitsupporting
confidence: 92%
“…In agreement with our results with lung surfactant, no graft related adverse events were found with amniotic membrane treatment in diabetic foot ulcers 54 , epidermolysis bullosa 55 or in burns 56 . Enhancement of granulation tissue formation and wound closure of arteriosclerotic foot sores or amelioration of atopic dermatitis by topical Alv treatment are preliminary observations of a pilot study that will be investigated in the next phase of clinical trials.…”
Section: Visitsupporting
confidence: 92%
“…No adverse events were recorded, including infection—a common complication occurring in up to 18% cases post OPF [ 3 ]. Pain reduction of 8/10 to 0/10 led to reduced use of narcotics post-surgery, a phenomenon also reported in burn hand cases treated with vCPM [ 6 ].…”
Section: Discussionmentioning
confidence: 76%
“…Here, vCPM was applied proximally in the surgical dissection space over the MCP joint with the goal of preventing contracture reoccurrence. Previously reported data showed that vCPM application to a hand burn resulted in absence of contracture with ROM restoration and absence of scar reformation when used as an adjunct to chronic keloid resection [ 6 , 7 ]. Notably in this DD patient, the distal part of the surgical incision without vCPM underlay required triamcinolone injection due to post-op fascia thickening.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it would act as a sustained delivery system of growth factors, which are key factors in wound healing regulation, and their exogenous administration has been proven to accelerate healing [ 35 ]. Examples of cells containing skin substitutes would be Apligraf ® , bovine type I collagen seeded with allogeneic neonatal foreskin fibroblasts and keratinocytes; Dermagraf ® , synthetic polyglycolic or polylactic acid (PGA orPLA), ECM and allogeneic neonatal foreskin fibroblasts; or GRAFIX-Prime (viable cryopreserved placental membrane), which are clinically indicated for chronic wounds, such as diabetic foot ulcers, and partial and full thickness burns [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%